1995
DOI: 10.1002/jmv.1890460110
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with interferon alpha‐2b and ribavirin for chronic hepatitis C in patients with a previous non‐response or non‐sustained response to interferon alone

Abstract: Ten patients with chronic hepatitis C, six of whom had not responded and four of whom had responded in a non-sustained fashion to interferon-alpha treatment alone, were given interferon alpha-2b and ribavirin in combination during 24 weeks. Interferon alpha-2b was given subcutaneously, at a dose of 3 MU thrice weekly, together with ribavirin orally, at a dose of 1,000-1,200 mg/day. All four patients with a prior non-sustained response to interferon alone had normal alanine aminotransferase (ALT) levels at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
54
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 18 publications
1
54
0
1
Order By: Relevance
“…After three washes with PBS-T, the standards and appropriately diluted samples were mixed with peroxidase-conjugated human albumin (final concentration 50 ng/mL), added to antibody coated wells and incubated for one hour at 37°C. Plates were washed three times with PBS-T and 100 µL of peroxidase substrate solution (citrate-phosphate buffer [pH 5.0] containing 0.4 mg of O-phenylenediamine/mL and 0.01% H 2 O 2 [vol/vol]) was added to each well. Color development was stopped by the addition of 50 µL of 2.5 mol/L sulfuric acid and plates were read at 492 nm using a microplate photometer (Titertek Multiscan MCC/340, Labsystems, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…After three washes with PBS-T, the standards and appropriately diluted samples were mixed with peroxidase-conjugated human albumin (final concentration 50 ng/mL), added to antibody coated wells and incubated for one hour at 37°C. Plates were washed three times with PBS-T and 100 µL of peroxidase substrate solution (citrate-phosphate buffer [pH 5.0] containing 0.4 mg of O-phenylenediamine/mL and 0.01% H 2 O 2 [vol/vol]) was added to each well. Color development was stopped by the addition of 50 µL of 2.5 mol/L sulfuric acid and plates were read at 492 nm using a microplate photometer (Titertek Multiscan MCC/340, Labsystems, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…31,32 These include case selection, higher dose of IFN, 14,15,18,19,21,[33][34][35] increased duration of therapy, 17,18,22,[35][36][37][38] and use of adjunctive agents. [39][40][41] Less attention has been given to possible differences between IFN preparations, although it has been shown that IFN-␥ is ineffective against hepatitis C. 33 The alpha and beta IFNs act through the same cellular receptors. There are 13 separate human alpha-IFN gene loci that code for approximately 25 IFN subtypes and molecular variants; they differ in their amino acid sequence and are subject to varying degrees of glycosylation.…”
mentioning
confidence: 99%
“…2,3 Thus, retreatment of nonresponders with IFN alone generally is considered ineffective. 4 Pilot studies 5,6 using ribavirin (a broad-spectrum antiviral drug given by mouth) with IFN have reported sustained responses in approximately 40% of patients who had a relapse or no response to IFN alone. Further studies have shown that the response to combination therapy is significantly different between patients who had no response to IFN and those who had a response while undergoing therapy but then relapsed; with combination therapy a sustained response is observed in most relapsers but in only few nonresponders.…”
mentioning
confidence: 99%